The Impact of Ileostomy-Related Complications on the Multidisciplinary Treatment of Rectal Cancer - Phatak, Uma R. (2013)
BACKGROUND: Radical resection is the primary treatment for rectal cancer. When anastomosis is possible, a temporary ileostomy is used to decrease morbidity from a poorly healed anastomosis. However, ileostomies are associated with complications, dehydration, and need for a second operation. Our purpose was to evaluate the impact of ileostomy related complications on the treatment of rectal cancer. METHODS: A retrospective cohort study of patients who underwent sphincter preserving surgery between January 2005 and December 2010 at a tertiary cancer center. The primary outcome was the overall rate of ileostomy related complications. Secondary outcomes included complications related to ileostomy status, ileostomy closure, anastomotic complications at primary resection, rate of stoma closure, and completion of adjuvant chemotherapy. Statistical analyses were performed with STATA 12. RESULTS: A total of 294 patients were analyzed, 32% (n=95) were women. Two hundred seventy-one (92%) received neoadjuvant chemoradiation. The median tumor distance from the anal verge was 7 centimeters (interquartile range 5-10). Two hundred eighty-one (96%) underwent stoma closure at a median 7 months (interquartile range 5.4 – 8.3). The most common complication related to readmission was dehydration (n=32, 11%). Readmission within 60 days of primary resection was associated with delay in initiating adjuvant chemotherapy (OR 3.01, 95% CI 1.42-6.38, p=0.004). CONCLUSION: Diverting ileostomies created during surgical treatment of rectal cancers are associated with morbidity; however this is balanced against the risk of anastomosis-related morbidity at rectal resection. Given the potential benefit of fecal diversion, patient-oriented interventions to improve ostomy management, particularly during adjuvant chemotherapy, can be expected to yield marked benefits.